Home visit: an educational health strategy for self-care in diabetes - Heloisa de Carvalho Torres; Laura Maria dos Santos; Palloma Maciel Chaves de Souza Cordeiro (Escola Paulista de Enfermagem, Universidade Federal de São Paulo, 2014)
OBJECTIVE: To understand the home visit as an educational health care strategy to orient the self-care practices of patients with type 2 diabetes mellitus.METHODS: A qualitative study using 25 home visits to patients with diabetes mellitus, who did not attend the diabetes education program offered by the basic health care unit. Data were organized and categorized by content analysis.RESULTS: Four thematic categories emerged: feelings; knowledge about the disease; adherence to meal plan and physical activity; and barriers to self-care.CONCLUSION: Home visit is an important strategy for health care education to orient patients with type 2 diabetes on self-care practices.